Pengaruh Media Audio Visual Terhadap Pengetahuan Sepak Bola Siswa Kelas IV Mi Ma’arif Mangunranan Mirit Kebumen Tahun 2020 - Prasetyo Widiyono, Ibnu; Nurudin (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
This research is an experimental research, namely the research method used to find the effect of certain treatments on others under controlled conditions. With the type of design used is one group pretest and posttest design. Then take the title The Effect Of Audio Visual Media On Soccer Knowledge For The Four Grade Students Of Mangunranan Mirit Kebumen In The Academic Year Of 2020. The objectives of the research are: to find out about increasing soccer knowledge the four grade students of MI Maárif Mangunranan. This research is a eksperimen research. Subjects of this research were 25 students of MI Ma’arif Mangunranan. Sources of data were obtained from pre-test, treatment, and post-test. The results of the research show that, there is a significant influence of the use of audio-visual media on soccer knowledge for the four grade students of Mangunranan Mirit Kebumen in the academic year of 2020. With the results at the time of the post test have a good level of knowledge of soccer categories. In detail, as many as 0 students (0%) had a very low category, 0 students (0%) had less categories, 5 students (20%) had a moderate category, 15 students (60%) had a good category, and 5 students (20%) ) has a very good category. The highest frequency is in the interval class 71-80 or in either category. The conclusion of this research is there is a significant influence of the use of audio-visual media on soccer knowledge for the four grade students of Mangunranan Mirit Kebumen in the academic year of 2020. Keywords: Audio Visual, Knowledge, Soccer